2003
DOI: 10.1007/bf02723826
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood stem cell banking and transplantation

Abstract: Stem cells have the ability to divide for indefinite periods in culture and to give rise to specialized cells. Cord blood as a source of hematopoietic stem cells (HSC) has several advantages as it is easily available, involves non-invasive collection procedure and is better tolerated across the HLA barrier. Since the first cord blood transplant in 1988, over 2500 cord blood HSC transplants have been done world wide. Since then, the advantages of cord blood as a source of hematopietic stem cells for transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…From the results of RT-PCR, Northern blot and Slot blot analysis, we found that all these malignant tumor tissues, benign tumor tissues, and benign hyperplastic tissues had high levels of NS expression, which indicated that NS played an important role in the selfrenewal of these cancer cells and hyperplastic cellls. At the same time, NS expressed in human placental tissues also at a high level, possibly due to the existence of a mass of placental stem cells [20][21][22][23] . A small quantity of NS expression could be found in normal human muscle tissues by RT-PCR, however no expression could be detected by Slot blot and Northern blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of RT-PCR, Northern blot and Slot blot analysis, we found that all these malignant tumor tissues, benign tumor tissues, and benign hyperplastic tissues had high levels of NS expression, which indicated that NS played an important role in the selfrenewal of these cancer cells and hyperplastic cellls. At the same time, NS expressed in human placental tissues also at a high level, possibly due to the existence of a mass of placental stem cells [20][21][22][23] . A small quantity of NS expression could be found in normal human muscle tissues by RT-PCR, however no expression could be detected by Slot blot and Northern blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] In addition, human HSCs are defined by their ability to replenish all blood cell types and their ability to self-renew, containing both multipotent and lineage committed progenitors which give rise to all the blood cell types. 47 The presence of HSCs in cord blood is an attractive cell source that is readily available and can be collected noninvasively with a lower occurrence of cytomegalovirus infection. 48 Moreover, HSCs extracted from cord blood for transplantation have been widely used, and are capable of decreasing human leukocyte antigen ͑HLA͒ mismatches from a related family donor.…”
Section: Adult Stem Cellsmentioning
confidence: 99%
“…5 The Rh (not Rhesus) system is the second most important blood group system in transfusion medicine because antigen-positive RBCs frequently immunize antigen-negative individuals through transfusion and pregnancy. [4][5][6] ABO and Rh gene phenotypes differ widely across races and geographical boundaries [7][8][9] . Many studies were carried out on the frequency of ABO and Rh phenotypes in different populations 10 .…”
Section: Introductionmentioning
confidence: 99%